From Content To Continuity: The Role Of Engagement In Building Customer Stickiness On Social Media - Nurfitri, Istiqomah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study investigates how social media content shapes sustained consumer behavior in the bodycare industry by examining the roles of Relational Content (RLC) and Remunerative Content (REC) in driving Customer Engagement (CN), Customer Loyalty (CL), and Customer Stickiness (CS). A cross-sectional survey involving 220 Instagram users of Scarlett bodycare products was analyzed using PLS-SEM in SmartPLS 4. All measurement constructs met validity and reliability standards. The results reveal that both RLC and REC significantly enhance engagement and stickiness, with relational cues showing consistently stronger effects than transactional incentives. Engagement emerges as the most influential predictor of stickiness and also strongly contributes to loyalty, whereas loyalty does not significantly predict stickiness. These findings indicate that sustained platform use is more strongly driven by active engagement behaviors than by attitudinal loyalty alone. Practically, brands should prioritize relational content—such as storytelling, empathy, and community interaction—to cultivate deeper involvement, while using promotional content strategically to prompt initial or repeated participation. The study advances content marketing and engagement literature by demonstrating the superiority of relational cues over extrinsic rewards in fostering long-term behavioral continuity on social media. Limitations include the use of a single-brand context and cross-sectional design. Future studies may extend the model to other industries, platforms, or longitudinal settings to further examine how engagement evolves into loyalty and behavioral persistence.